2006
DOI: 10.1111/j.1399-6576.2006.01100.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory effect of high‐dose insulin treatment after urgent coronary revascularization surgery

Abstract: Background: The administration of insulin has been shown to exert cardioprotective and immunomodulatory properties. Ischemia and inflammation are typical features of acute coronary syndrome, thus it was hypothesized that high-dose glucoseinsulin-potassium (GIK) treatment could suppress the systemic inflammatory reaction and attenuate myocardial ischemiareperfusion injury in patients with unstable angina pectoris after urgent coronary artery bypass surgery. Methods: Forty patients with unstable angina pectoris … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 23 publications
0
19
0
1
Order By: Relevance
“…Insulin also has anti-inflammatory properties, 121,122 and strict blood sugar control by means of insulin infusion may contribute to reduced cytokine activation after brain death. 123 However, the main issue in this connection is the use of steroids.…”
Section: Hemodynamic Managementmentioning
confidence: 99%
“…Insulin also has anti-inflammatory properties, 121,122 and strict blood sugar control by means of insulin infusion may contribute to reduced cytokine activation after brain death. 123 However, the main issue in this connection is the use of steroids.…”
Section: Hemodynamic Managementmentioning
confidence: 99%
“…Small, mechanistic studies have suggested that insulin may have anti-inflammatory, pro-fibrinolytic and anti-apoptotic properties, and that it can inhibit generation of reactive oxygen species and improve myocardial blood flow. [40][41][42][43][44][45][46][47][48] However, whether insulin therapy is associated with any clinical benefit in AMI above and beyond its associated glucose-lowering effect remains a subject of debate. One observational study demonstrated that patients with severe hyperglycaemia on admission (> 11.0 mmol/L [~200 mg/dL]) and no prior history of diabetes had a 56% relative risk increase in mortality at seven days (and a 51% increase in mortality at 30 days) if they did not receive insulin during hospitalisation, as compared with similar patients who did receive insulin therapy.…”
Section: Is There Evidence That Glucose Lowering During Ami Hospitalimentioning
confidence: 99%
“…Small, mechanistic studies suggested that insulin may have antiinflammatory, profibrinolytic, and antiapoptotic properties and can inhibit the generation of reactive oxygen species and improve myocardial blood flow. [37][38][39][40][41][42][43][44][45] However, whether group. However, to definitively determine whether hyperglycemia is directly harmful, well-designed randomized clinical trials of target-driven intensive glucose control in hospitalized AMI patients are needed.…”
Section: Relationship Between Insulin Therapy and Outcomes In Hyperglmentioning
confidence: 99%
“…Small, mechanistic studies suggested that insulin may have antiinflammatory, profibrinolytic, and antiapoptotic properties and can inhibit the generation of reactive oxygen species and improve myocardial blood flow. [37][38][39][40][41][42][43][44][45] However, whether randomized hyperglycemic patients (average glucose at randomization >275 mg/dl) to either standard therapy or intravenous glucose-insulin infusion titrated to achieve a prespecified target of 126-196 mg/dl during the acute phase, followed by multidose subcutaneous insulin injections for 3 months. Following randomization, clinically and statistically lower glucose levels were achieved in the glucose control patients (≈173 mg/dl) versus control (≈211 mg/dl) at 24 hours, and a significant difference was maintained through discharge.…”
mentioning
confidence: 99%